2003
DOI: 10.1002/mpo.10257
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of all‐trans‐retinoic acid in children with acute promyelocytic leukemia

Abstract: Considering the low plasma concentrations and the persistence of toxicity in spite of dose reduction intermittent dosing schedules might be considered as an alternative to further dose reduction of ATRA in the treatment of APL especially in children, who might be at risk of ATRA-induced neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
0
21
1
Order By: Relevance
“…Lanvers et al found that the plasma retinol level is related to ATRA-induced neurotoxicity in children [4]. In the present study, however, there was no difference of retinol levels between children with and without neurotoxicity (data not shown).…”
Section: Pharmacokinetics Of All-trans Retinoic Acid In Adults and Chcontrasting
confidence: 74%
“…Lanvers et al found that the plasma retinol level is related to ATRA-induced neurotoxicity in children [4]. In the present study, however, there was no difference of retinol levels between children with and without neurotoxicity (data not shown).…”
Section: Pharmacokinetics Of All-trans Retinoic Acid In Adults and Chcontrasting
confidence: 74%
“…Oxidative metabolism has previously been observed in studies with ATRA (Muindi et al, 1992;Rigas et al, 1993) and fenretinide (Villani et al, 2004), and auto-induction of oxidative metabolism has been associated with disease relapse, following chronic administration of ATRA in APL (Muindi et al, 1992). This can be avoided by the use of intermittent ATRA dosing schedules (Adamson et al, 1995), an approach that has also been recommended to minimise the side effects of ATRA in children (Lanvers et al, 2003). Our results with 13-cisRA show an accumulation of the 4-oxo-metabolite between days 1 and 14 of treatment in all patients, with metabolite concentrations higher than those of the parent drug by day 14 in approximately 70% of patients.…”
Section: Discussionmentioning
confidence: 71%
“…The dosing regimen of 80 mg m À2 twice daily for 14 days was associated with significant inter-patient variation in 13-cisRA pharmacokinetics, comparable with that observed following ATRA administration for the treatment of APL (Lanvers et al, 2003). For 13-cisRA, pharmacokinetics may be influenced by a number of factors, including both the method of drug administration and the extent of metabolism.…”
Section: Discussionmentioning
confidence: 72%
“…With this regimen, the hematologic complete remission (HCR) rate has improved significantly, to more than 90%; 5-year disease-free survival is more than 70%. [5][6][7][8][9][10] However, some problems still remain; notably, ATRA-related side effects appear to be more pronounced in children than in adult patients, 4,[11][12][13] the optimal postremission therapy still remains to be defined, and approximately 20% to 30% of patients eventually relapse and develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%